Convergent minds: ostension, inference and Grice's third clause. Issue 3 (21st April 2017) - Moore, Richard
Abstract : A prevailing view is that while human communication has an 'ostensive-inferential' or 'Gricean' intentional structure, animal communication does not. This would make the psychological states that support human and animal forms of communication fundamentally different. Against this view, I argue that there are grounds to expect ostensive communication in non-human clades. This is because it is sufficient for ostensive communication that one intentionally addresses one's utterance to one's intended interlocutor—something that is both a functional pre-requisite of successful communication and cognitively undemanding. Furthermore, while ostension is an important feature of intentional communication, the inferences required in Gricean communication may be minimal: ostension and inference may come apart. The grounds for holding that animal communication could not be Gricean are therefore weak. I finish by defending the idea that a 'minimally Gricean' model of communication is a valuable tool for characterizing the communicative interactions of many animal species.